Headmaster Management Pattern in Improving Teacher Competence at SMA Muhammadiyah 1 Ponorogo - Ahmad Fikri; Syarifah Syarifah (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
Leaders are at the core of management. This means that management will achieve its objectives if this leader is able to direct and coordinate group members within the objectives. The principal as the implementer is responsible for the implementation of educational activities, school administration, coaching other educational personnel, and utilization and maintenance. The research used is descriptive method. And to achieve this goal the author uses an approach method that is qualitative so that the data collected is in the form of data and sentences. therefore this research is descriptive qualitative so to get good research results then the author uses interviews, observations and documentation as a support in collecting data in this study. Findings in this study shows the management pattern of the principal in improving the competence of teachers at SMA Muhammadiyah 1 Ponorogo, the principal used planning management in the recruitment process by conducting selections to prospective teachers. And the principal also uses academic supervision of teachers and conducts training programs such as workshops for the entire teacher council. and also found the existence of factors that support the development and inhibition of improvement in teacher competence.